2008
DOI: 10.1016/j.clinph.2008.07.284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluctuating physiological rhythms during prolonged EEG-fMRI studies

Abstract: Objective-We evaluated BOLD correlates of alertness fluctuations commonly seen during prolonged EEG-fMRI studies to better define the brain areas active at different phases of vigilance and to assess the contribution of these fluctuations to the BOLD signal.Methods-We evaluated BOLD changes specifically related to the main physiological EEG rhythms (alpha, beta, theta, delta, spindles) in 15 epilepsy patients with rare discharges (all the regressors were included in the same general linear model to improve spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
95
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 50 publications
30
95
1
5
Order By: Relevance
“…These authors observed a correlation between an increase in occipital alpha power and a decrease in fMRI blood oxygenation level-dependent (BOLD) signals in the occipital, superior temporal, inferior frontal, and cingulate cortices and with an increased hemodynamic response in the thalamus. Other EEG-fMRI results supported this finding (DiFrancesco et al 2008, Feige et al 2005, Liu 2012, Moosmann et al 2003, de Munck et al 2007, Tyvaert et al 2008. Interestingly, some published results seemed to confirm increases (Ben-Simon et al 2008) or decreases (Goldman et al 2002, Moosmann et al 2003 of the BOLD signal in anterior brain regions together with increases of alpha EEG activity in frontal recordings, but these relationships were not discussed in detail by the authors.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…These authors observed a correlation between an increase in occipital alpha power and a decrease in fMRI blood oxygenation level-dependent (BOLD) signals in the occipital, superior temporal, inferior frontal, and cingulate cortices and with an increased hemodynamic response in the thalamus. Other EEG-fMRI results supported this finding (DiFrancesco et al 2008, Feige et al 2005, Liu 2012, Moosmann et al 2003, de Munck et al 2007, Tyvaert et al 2008. Interestingly, some published results seemed to confirm increases (Ben-Simon et al 2008) or decreases (Goldman et al 2002, Moosmann et al 2003 of the BOLD signal in anterior brain regions together with increases of alpha EEG activity in frontal recordings, but these relationships were not discussed in detail by the authors.…”
Section: Introductionsupporting
confidence: 67%
“…Other researchers have used the eyes-closed condition across the entire EEG session (a "resting state experiment" (DiFrancesco et al 2008, Goldman et al 2002, Laufs et al 2003, Mantini et al 2007, Moosmann et al 2003, de Munck et al 2007, Mantini et al 2007, Scheeringa et al 2012, Tyvaert et al 2008. The latter paradigm prevents BOLD signal variation due to visual stimulation but precludes comparisons of the results with experiments searching for neuronal mechanisms underlying the Berger effect (Berger 1929).…”
Section: General Methodological Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…This result might potentially represent a typical feature of [r (20)] syndrome, as the physiologic hemodynamic correlates of theta-delta activity are mainly represented by negative BOLD changes over the associative frontoparietal cortices. [28][29][30] Furthermore, we observed that the power of the slow-wave rhythm negatively correlated with the BOLD signal within the DMN and the DAN. This finding indicates that the higher the expression of the rhythm, the greater the decrease of activity within the DMN and the DAN.…”
Section: ] Syndromementioning
confidence: 64%
“…Using such methods, several studies have examined the association between fluctuations in the frequency power of spontaneous EEG activity and BOLD signals obtained using fMRI (Goldman et al, 2002;Jann et al, 2009;Laufs et al, 2003;Mantini et al, 2007;Tyvaert et al, 2008). These studies have revealed that oscillations in the different frequency bands contribute differentially to the BOLD signal.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%